Heat transfer analysis from moving convection-radiative triangular porous fin exposed to heat generation - Ikram Ullah; Sharif Ullah; Amir Ali; Syed Irfan Shah; Wajaree Weera; Mohammad Mahtab Alam (Case Studies in Thermal Engineering, 2022)
The aim of this work is to analyze the enhancement in the heat transfer and investigate the efficiency of moving, porous and triangular fins. The influence of the various dimensionless parameters, like porosity, radiation-conduction, Peclet number, thermo-geometric parameters, convection-conduction, and surface temperature are analyzed on the efficiency of moving, porous and triangular fins. The model is investigated numerically as well as analytically by using DTM. The result is compared to check the accuracy of the semi-analytical solution, where good agreement is obtained. The effects of the considered parameters on the temperature distribution and efficiency of the considered fins are studied to investigate better efficiency, which plays a significant role in mechanical engineering.